Cambios en la agricultura y su impacto en el desarrollo del caserío de Coina–Otuzco, La Libertad, 2013 - López Rodríguez, Nancy Isela (2014)
The hamlet of Coina, is a farming community, who created their own strategies for seeding, harvesting and marketing, it has also been able to maintain its leadership for many years as a producer of fruits in the most popular markets in the cities on the coast. Coina, have enough water for the cultivation of their lands. In recent times, has been negatively deepening the gap between the shortage of land resources and population growth, due to the constant migration of “farm people ". Families choose to migrate to Coina Heights, motivated by the education of their children, others for job opportunities in agriculture, construction and mining. We also identify the existing water gap, given that the apparent absence of plans for small irrigation infrastructure in the highlands to retain water. These lands survive with irrigation channels crafts made by the residents of Coina own. This research is aimed to explain the changes in agriculture and its impact on the development of Coina to explain the phenomena that have led to the gradual abandonment of agricultural activity in three main aspects: 1. The migration of farm people: residents of communities surrounding the village , leaving their land to live in the village, motivated by their children's education and job opportunities in mining and construction 2. Migration from village to city: this can be seen in the output of the villagers to the cities in search of their professional training, economic improvements and living conditions 3. Large investments (Capitalism and globalization): Mining companies like Barrick, provide employment to villagers outside the village, local, regional and national governments with their social programs, provide immediate employment to farmers sow to stop working for pay. ONGs: World Vision, Manuela Ramos, among others applies their social programs and open new opportunities for employment and income.